Pirelli & SpA : equity valuation research - Macedo, Diogo Gaspar de Lacerda (2020)
The goal of this academic dissertation is assessing the correct value of Pirelli & SpA’s shares on the 31st December of 2019. Two distinct valuation methods are applied, the first being the Discounted Cash Flow (DCF) approach and the second being the relative valuation methodology, with the multiples used being the P/E, EV/EBITDA and EV/Sales. Then, the result yielded by the valuation approaches is compared to an equity research report made by Banca IMI. The conclusion of this dissertation is that Pirelli is marginally undervalued in the market, being the fair value of one unit of common stock estimated to be €5.28 at the end of 2019, while the share is trading at €5.15 on the 29th November of 2019. Hence, the recommendation given in this dissertation is that investors should buy Pirelli’s shares. This recommendation is solely based on the DCF methodology, since the relative valuation produced inconsistent results across the different multiples used and when compared with the value computed through the DCF approach. Banca IMI estimates the value of one unit of common stock at the end of 2019 to be €6.10, which is a higher valuation than the one expected by this dissertation. As Netflix’s stock was trading at €5.41 at the time of valuation, Banca IMI also advises to buy Pirelli’s stock. This difference can be justified by different assumptions regarding the evolution of Netflix’s FCFFs and Perpetual growth, as the WACC in both valuations differs only 24 basis points.